Aluminum tolerance and micronutrient content in the grain of oat cultivars with different levels of breeding improvement from the VIR collection - I. G. Loskutov; V. Butris; I. A. Kosareva; E. V. Blinova; L. Yu. Novikova (Труды по прикладной ботанике, генетике и селекции)
Background. Soil toxicity of Al is associated with severe changes in plant root morphology that limit the uptake of water and mineral nutrients. Long-term exposure to Al results in deficiencies in some important nutrients, such as phosphorus, calcium, magnesium, potassium, and iron. Thus, the joint study of plant resistance to the effects of Al and the accumulation of micronutrients in the oat grain is relevant.Materials and methods. Thirty oat accessions of Russian and French origin from the VIR collection served as the research material. They were represented by cultivars with different levels of breeding improvement: landraces (early 1920s), cultivars developed by primitive breeding (1920–1930s), and modern improved cultivars.Results. Oat cultivars with different breeding improvement levels demonstrated significant differences in the content of micronutrients and aluminum tolerance. Among the studied accessions, landraces and modern improved cultivars showed a tendency towards medium or high Al tolerance, the group of primitive cultivars from Russia had the lowest Al tolerance, while primitive cultivars from France demonstrated the highest average resistance (0.5–1.9).Conclusion. The content of Fe and Zn was influenced by the geographic origin of genotypes. The concentrations of different micronutrients positively correlated with each other. Strong correlations were recorded between the contents of Zn and Fe (r = 0.81), and between Zn and Mg (r = 0.75). There was a positive correlation between the content of micronutrients and the resistance to crown rust (0.38 to 0.50). High content of the studied set of micronutrients was registered in such improved cultivars from France as the naked ‘Avoine Nue Renne’, ‘Chantilly’, ‘Negrita’ and ‘Noire de Michamps’, plus the Russian improved naked cultivar ‘Gavrosh’. Among them, ‘Chantilly’ was distinguished for its yield, and the naked ‘Gavrosh ‘for its high tolerance to aluminum.